Chlamydia and Gonorrhea Incidence and Testing Among Patients in the Human Immunodeficiency Virus Outpatient Study (HOPS), 2007−2017. (6th November 2019) - Li, Jun; Armon, Carl; Palella, Frank J; Novak, Richard M; Ward, Douglas; Purinton, Stacey; Durham, Marcus; Buchacz, Kate
Abstract: Background: Although chlamydia (CT) and gonorrhea (GC) infections are increasing in the United States, there are limited data on their incidence, testing rates, and associated risk factors among persons living with HIV (PLWH), including by anatomic site among men who have sex with men (MSM). Methods: We analyzed 2007–2017 medical records data from Human Immunodeficiency Virus (HIV) Outpatient Study (HOPS) participants in care at 9 HIV clinics. We calculated CT (and GC) incidence and testing rates and assessed associations with sociodemographic and clinical factors using log-linear regression. Results: Among 4727 PLWH, 397 had 881 CT infections and 331 had 861 GC infections, with an incidence of 2.95 and 2.88 per 100 person-years, respectively. From 2007 to 2017, incidence and testing rates increased by approximately 3.0- and 1.9-fold for CT and GC, respectively. Multivariable factors associated with incident CT (GC) included younger age, MSM, and prior diagnoses of sexually transmitted diseases (STDs). Among 1159 MSM, 583 (50.3%) had 844 CT and 843 GC tests during 2016–2017, and 26.6% of tests were 3-site (urethra, rectum, and pharynx), yielding the highest rates of CT (GC) detection. Multivariable factors associated with CT (GC) testing included younger age, non-Hispanic/Latino black race, and having prior STDs. Conclusions: Recent CT and GC incidence and testing increased among PLWH; however, only half of MSM were tested for CT or GC during 2016–2017 and less than a third of tests were 3-site. To promote sexual health and STD prevention among PLWH who are MSM, research regarding the added value of CT and GC testing across 3 anatomic sites is needed. Abstract : Only half of Human Immunodeficiency Virus-positive men who have sex with men were tested for chlamydia (CT) or gonorrhea (GC), and less than a third of tests were 3-site. The added value of CT and GC testing across 3 anatomic sites warrants additional research.